How can neuroscience help understand design and craft activity? The promise of cognitive neuroscience in design studies - Seitamaa-Hakkarainen, Pirita; Huotilainen, Minna; Mäkelä, Maarit; Groth, Camilla; Hakkarainen, Kai (FormAkademisk, 2016)
Designing and making crafts is a complex, multifaceted process that requires sophisticated, professional thinking and competence, described as reflection in action and as an embodied process in which the hand, eye and mind collaborate. This article discusses these cognitive and embodied aspects central to designing and making crafts in light of cognitive neuroscience. Understanding the specific cognitive processes and forms of knowledge used in creative practices is essential. In this article, we propose that cognitive neuroscience provides valuable tools for analysing thinking and acting processes relevant to designing and making. We discuss the challenges and opportunities that the use of brain imaging methods, in particular, provides for understanding design activities, skills and cognition. Additionally, we present two neuroscientific experimental settings from our empirical studies in which the methods of cognitive neuroscience are applied to study and detect the interrelations between drawing, forming, skill learning and the functional activities of the brain and its subareas. We argue that cognitive neuroscience provides valuable instruments and methods which complement traditional design research.